Disobeying the Security Council countermeasures against wrongful sanctions - Tzanakopoulos, Antonios (Oxford : Oxford University Press, 2011)
In the last few years, the Security Council has imposed highly controversial sanctions on both individuals and states, some of which can be considered to violate international law. This book argues that the law of international responsibility allows states to disobey these obligations when they would result in a violation of human rights.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Includes bibliographical references and index.
Keywords: United Nations. -- Security Council; Sanctions (International law)